Ethnobotanical Study of Kaithal District Haryana, India: Exploring the Ethnobotanical Practices in Kaithal District, Haryana, India (Journal of Advances and Scholarly Researches in Allied Education, 2020)
All around the globe, ethnobotanical surveys based on the use of plants by the indigenous peoples have become more relevant. Many ethnobotanical studies have been conducted in India, both at the national and regional levels, as well as using a variety of approaches, including archaeological study in literature and field investigations. As part of the study, researchers are looking for plants that are utilised and altered by locals to treat different diseases. All, there are 71 ethnobotanical species, belonging to 67 genera and 38 families. Leguminosae has the most species, followed by Asteraceae, which has the fewest. Leaves, fruits, seeds, and roots are the most often utilised plant components in the pharmaceutical industry. The botanical name, family name, local name, plant part utilised, diversity status, and use value of each ethnomedicinal species are included in the medicinal plant database. ethnobotanical, ethnopharmaceutical studies, ethnomedicine and anthropology, ethnoagriculture and home, ethnoveterinary medicine, ethnomusicology, ethnobotanical and ethnobotanical studies were explored in this research. Generic and species counts for each family, Ethnobotanically significant plant genera and species,